2017
DOI: 10.1073/pnas.1714097114
|View full text |Cite
|
Sign up to set email alerts
|

Big data modeling to predict platelet usage and minimize wastage in a tertiary care system

Abstract: SignificanceIn modern hospital systems where complicated, severely ill patient populations are the norm, there is currently no reliable way to forecast the use of perishable medical resources to enable a smart and economic way to deliver optimal patient care. We here demonstrate a statistical model using hospital patient data to quantitatively forecast, days in advance, the need for platelet transfusions. This approach can be leveraged to significantly decrease platelet wastage, and, if adopted nationwide, wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 21 publications
3
64
1
Order By: Relevance
“…This current phase was to create a platform allowing automatic electronic ordering with some flexibility to adjust levels in real time; the manual process is simply too error prone. We have recently published on a mathematical algorithm to predict product usage days in advance so as to reduce wastage while never compromising patient care . We plan to incorporate this predictive model into the current electronic platform to further automate and control the inventory levels for continued optimal patient care, while also reducing wastage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This current phase was to create a platform allowing automatic electronic ordering with some flexibility to adjust levels in real time; the manual process is simply too error prone. We have recently published on a mathematical algorithm to predict product usage days in advance so as to reduce wastage while never compromising patient care . We plan to incorporate this predictive model into the current electronic platform to further automate and control the inventory levels for continued optimal patient care, while also reducing wastage.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently published on a mathematical algorithm to predict product usage days in advance so as to reduce wastage while never compromising patient care. 24 We plan to incorporate this predictive model into the current electronic platform to further automate and control the inventory levels for continued optimal patient care, while also reducing wastage. This whole system, comprising an electronic ordering system with a predictive algorithm for future use, has the potential to allow the BC to adjust its collections based on future demand.…”
Section: Discussionmentioning
confidence: 99%
“…This model, which they used to guide ordering and improve inventory management, reduced wastage from expiration by more than 7 percent, which has the potential to save 950 units each year while also avoiding shortages. 1 The researchers indicated that this strategy could also be easily applied to other blood products. 1 Fadeyi et al 12 implemented a hybrid transportation strategy using innovative blood cooler inserts that maintain RBC temperature for 10 hours and a real-time tracking device, along with education initiatives.…”
Section: Newer Strategiesmentioning
confidence: 99%
“…1 The researchers indicated that this strategy could also be easily applied to other blood products. 1 Fadeyi et al 12 implemented a hybrid transportation strategy using innovative blood cooler inserts that maintain RBC temperature for 10 hours and a real-time tracking device, along with education initiatives. When the cooler approached the 10-hour expiration limit, staff members at the blood bank determined its location and notified the appropriate personnel regarding how much time they had to return the RBCs.…”
Section: Newer Strategiesmentioning
confidence: 99%
See 1 more Smart Citation